Analisis Hukum Tentang Tindak Pidana Seksual Yang Terjadi Di Kota Medan (Study PutusanNomor : 1840/Pid.B/2014/PN.Mdn) - Adha, Mhd. Hendara; Warman, Edi; Eddy, Triono (Universitas Medan Area, 2020)
This article discusses how the law arrangements in the juvenile justice in the process of resolving the case, How restorative justice restrictions in law enforcement in Indonesia and How the application of Restorative justice law in the process of settlement of criminal case in Criminal Law in Indonesia. This type of research is normative juridical that describes reviewing and explaining and analyzing normative provisions associated with restorative justice applicable in Indonesia. From the above discussion that restorative justice in the settlement of criminal acts committed by children is very concerned in rebuilding relations after the occurrence of criminal acts, rather than exacerbate the rift between the perpetrators, victims and the community which is the character of the current modern criminal justice system. The restorative criminal justice process holds the view that realizing justice is not only a matter of government and criminality, but more than that it must provide justice in totality that can not ignore the interests and rights of victims and society. Implementation of the principle of restorative justice and the process of diversion as an effort to solve crimes committed by children in formal juridical has been set clearly and firmly in Law Number 11 Year 2012 about kids of justice.